THE EFFECT OF QUANTUM TEACHING ON STUDENTS’ ABILITY IN READING PROCEDURE TEXT - Nurbaidah, Nina; Irmayana, Aprida; Lubis, Lollo Rosa; Kamisah (JEC (Jurnal Edukasi Cendekia), 2026)
The objectives of this research are to find out: a the students’ ability in reading procedure text by using quantum teaching method, whether there is a significant effect of quantum teaching and on students’ ability in reading procedure text at the first grade of English Department Institut Pendidikan Tapanuli Selatan. The population of this research is 26 students of the first grade students of English Department Institut Pendidikan Tapanuli Selatan.. The samples of this research are 26 the first grade students of English Department Institut Pendidikan Tapanuli Selatan by using total sampling. This research uses the experimental method because the writer wants to try to use a new teaching method in teaching reading procedure text. The technique of collecting data is by giving observation sheet and test in multiple choices form for procedure text mastery to the respondents in order to measure their reading procedure text. The writer uses the formula of ttest to test the hypothesis. Through the hypothesis testing the writer found that ttest is greater than ttable (ttest>ttable). It means that there is a significant effect of quantum teaching on students’ ability to master procedure text.